2014
DOI: 10.1016/j.ymgmr.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 17 novel mutations in 40 Argentinean unrelated families with mucopolysaccharidosis type II (Hunter syndrome)

Abstract: Mucopolysaccharidosis type II (MPSII) is an X-linked lysosomal storage disorder caused by deficiency of the enzyme iduronate-2-sulfatase (IDS). The human IDS gene is located in chromosome Xq28. This is the first report of genotype and phenotype characterization of 49 Hunter patients from 40 families of Argentina. Thirty different alleles have been identified, and 57% were novel. The frequency of de novo mutations was 10%. Overall, the percentage of private mutations in our series was 75%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…(Pro120Arg)[27]Likely pathogenicc.592G>Ap. (Asp198Asn)ClinVar ID: 221210[1]Likely pathogenicc.589_592delp. (Pro197Thrfs*15)NovelPathogenicc.708G>Ap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pro120Arg)[27]Likely pathogenicc.592G>Ap. (Asp198Asn)ClinVar ID: 221210[1]Likely pathogenicc.589_592delp. (Pro197Thrfs*15)NovelPathogenicc.708G>Ap.…”
Section: Resultsmentioning
confidence: 99%
“…(Pro120Arg)Severe (P13)Severe to intermediate [27]; severe [33]c.592G>Ap. (Asp198Asn)Severe (P22)Severe [1]c.708G>Ap. (Lys236Lys)Mild (P21)Intermediate [49]c.1264 T>Cp.…”
Section: Resultsmentioning
confidence: 99%
“…There is a high allelic heterogeneity among genes associated with MPS, which is the main cause of the wide spectrum observed in these disorders and cannot always be correlated with residual enzyme activity [108]. To date, more than 2200 mutations have been reported in all 11 genes related to MPS, with the majority of individuals showing private mutations (~70%) [109,110]. This broad mutational spectrum is composed mostly by missense/nonsense variants (64.6%), followed by small deletion/insertions/indels (19.6%), splicing defects (8.1%), complex rearrangements (4%), gross deletion/insertion/indels (3.6%) and defects in regulatory regions (0.2%) (http://www.hgmd.cf.ac.uk/ac) ( Table 4).…”
Section: Molecular Genetics Analysesmentioning
confidence: 99%
“…Kosuga et al [ 9 ] and a host of other authors [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ] have found that deletions, recombination, frameshift and in most but not all cases, nonsense mutations are associated with severe forms of the disease. This literature also points to a subset of missense mutations that also lead to severe forms, while the majority of missense mutations result in attenuated disease.…”
Section: Introductionmentioning
confidence: 99%